Application of the Calcium Looping Process for Thermochemical Storage of Variable Energy - Atkinson, Kelly (Université d'Ottawa / University of Ottawa, 2021)
On May 11th, 2019, atmospheric CO2 levels reached 415 ppm, a number 40% higher than the maximum level ever reached in the 800 000 years prior to the Industrial Revolution. This rise can be directly attributed to human activity, and has been linked to global temperature increase and climate change. Net CO2 emissions continue to rise as economies grow, and in 2018 global emissions reached 37.1 Gt. In order to reach the climate targets identified in the 2015 Paris Agreement, some scientists estimate that the world will need to attain net-zero anthropogenic greenhouse gas (GHG) emissions by 2050. Achieving this goal will require deployment of multiple technologies across multiple sectors. Of particular importance will be reducing or eliminating emissions associated to energy production via combustion of fossil fuels, which account for over 80% of CO2 emissions in G20 countries. One method of achieving this is to displace fossil fuel electricity generation with renewable source generation. Canada currently has 12 GW of installed wind capacity, and although it is the country’s fastest-growing source of renewable electricity, widespread deployment is inhibited by technical challenges including the time variability and geographic dispersion of sources. A potential solution to overcome the challenges facing integration of renewables is grid-scale energy storage. Many storage technologies currently exist at various levels of maturity. Although currently low on the development scale, thermochemical energy storage (TCES) has gained significant interest due to its potential to offer low-cost, short- or long-term storage of high-temperature heat using non-toxic, abundant materials. Several recent works have focused on the potential to pair the calcium looping (CaL) process, which exploits the reversible calcination of calcium carbonate, with concentrated solar power (CSP). This would enable CSP to provide continuous power to the grid while receiving discontinuous solar input, and recent projects have predicted storage cycle efficiencies in the range of 38-46%. As an extension of the work done to date, this project proposes a novel configuration of the CSP-CaL process which may offer advantages over other proposed configurations, including a reduction in process equipment requirements, elimination of pressure differentials between vessels, and a reduction in compression duty during the energy discharge period. A process simulation of the proposed system shows that it is capable of offering comparable storage cycle efficiencies, with the overall efficiency being strongly dependent on the residual conversion of calcium oxide in the carbonator as well as on the efficiencies of the power cycles employed to discharge the stored energy. In addition to the technical challenges that may come with this type of system, social and economic barriers may arise due to the fact that it will require large-scale storage of CO2, mining of natural limestone, and potentially large and complex facilities. All of these challenges must be considered and addressed in order to achieve deployment of this technology within Canada and around the world.
Keywords: Energy storage; Calcium looping